Stress-strain prediction in granitic residual soil by effective stress and shear strength interaction model / Abdul Samad Abdul Rahman - Abdul Rahman, Abdul Samad (2019)
This study focused on the prediction of soil stress-strain response under any arbitrary confining effective pressure. The stress-strain curves showed a higher peak strength as effective confining pressure increases. Therefore, there is a need for an effective method to predict the stress-strain response at any arbitrary effective confining pressure in order to carried out the soil volume change or settlement modelling. This is because the soil stress-strain behaviour governs the way the soil response to stress and influence the development of the mobilised shear strength envelopes. Thence, in soil volume change or settlement modelling, the most important property and the primary governing factor is the soil stress-strain response. Therefore, there is a need for accurate prediction of the stress-strain response at any specific value of effective stress. A method called Rotational Multiple Yield Surface Framework has been introduced for the prediction of the soil stress-strain response for saturated and unsaturated conditions. This is the concept of effective stress and shear strength interaction which is an extended concept of effective stress introduced by Terzaghi in 1936. The mobilised shear strength envelopes of the soil are derived from a minimum of three (3) stress-strain curves at three (3) different confining pressures. The limitation of the method is that it can only predict up to the minimum axial strain at failure and thus it cannot predict the stress-strain curve for the higher confining pressures. Then, in this study an improvised method has been introduced to overcome this limitation. The method is called Normalised Strain Rotational Multiple Yield Surface Framework. The test soil is granitic residual soil grade V taken from Kuala Kubu Baru and four (4) consolidated drained triaxial tests have been conducted at effective confining pressures of 50, 100, 200 and 300 kPa for saturated specimens and similar test at suction of 50, 100, 150, 200 and 250 kPa has been conducted for unsaturated specimens and the curve surface envelope of the soil has been determined to encompass the shear strength at saturated and unsaturated conditions. In addition, the effect of soaking in the degradation of soil shear strength of the test soil has also been investigated and essentially the strength reduce with the period of the soaking. Then the development of the mobilished shear strength envelop has been derived from the stress-strain curves. The determination of mobilished shear strength envelopes are the soil inherent property and it can be applied to predict the stress-strain response at any arbitrary effective confining pressure and at any value of suctions. The prediction of the stress-strain response using Normalised Strain Method is proved to improve the accuracy compared to the former Rotational Multiple Yield Surface Framework.